Association between Physical Activity Frequency and Hypertension Incidence among Indonesian Adults based on Indonesian Family Life Survey Wave 4 and 5 - Ardiani, Safirah Dina; Farapti, Farapti; Isaura, Emyr Reisha (Journal of Public Health for Tropical and Coastal Region, 2023)
Introduction: Hypertension incidence among adults in Indonesia increase every year. Many factors affect blood pressure, such as lifestyle which include diet and physical activity. This research aimed to analyse the association between physical activity frequency and hypertension incidence in Indonesia.Methods : This study used secondary data from Indonesian Family Life Survey Wave 4 and 5 held in 2007 and 2014, respectively from 257 adults. The subjects in this study had completed data on blood pressure, socioeconomic, and physical activity in both waves. The hypertension incidence was assessed using health practitioners’ diagnosis. Data analysis was conducted in logistic regressions.Results: There were differences in age, education level, systolic blood pressure (SBP), diastolic blood pressure (DBP), hypertension stage, and physical activities frequencies between IFLS4 data (2007) and IFLS5 data (2014) of the same subjects, with the p-values of <0.001. All of the physical activity frequencies (walk, moderate and vigorous) has no correlation with systolic blood pressure. The vigorous physical activity was positively correlated with diastolic blood pressure in both unadjusted (p=0.029) and adjusted analysis (p=0.017). Conclusion: The frequency of physical activity (walk, moderate, and vigorous) was not correlated to systolic blood pressures, but vigorous physical activity was positively correlated to diastolic blood pressure. For hypertension prevention, vigorous physical activity need to be reduced into moderate activities.